Call the midwife [compact disc, unabridged] : a memoir of birth, joy, and hard times - Worth, Jennifer, 1935-2011 (Highbridge Co., 2012)
At the age of twenty-two, Jennifer Worth leaves her comfortable home to move into a convent and become a midwife in post war London's East End slums. The colorful characters she meets while delivering babies all over London - from the plucky, warm-hearted nuns with whom she lives to the woman with twenty-four children who can't speak English, to the prostitutes and dockers of the city's seedier side - illuminate a fascinating time in history.